Self-reported hearing loss in Russians: the population-based Ural Eye and Medical Study - Bikbov, Mukharram; Fayzrakhmanov, Rinat R.; Kazakbaeva, Gyulli M.; Zainullin, Rinat M.; Salavatova, Venera F.; Gilmanshin, Timur R.; Arslangareeva, Inga I.; Nikitin, Nikolai A.; Panda-Jonas, Songhomitra; Mukhamadieva, Svetlana R.; Yakupova, Dilya F.; Khikmatullin, Renat I.; et al. (BMJ open, 2019)
Objective With data on frequency of hearing loss in Russia and Eastern Europe generally lacking, we assessed the prevalence of hearing loss in a Russian population. - Setting The population-based Ural Eye and Medical Study was conducted in the rural and urban regions of Bashkortostan, Russia. - Participants With an inclusion criterion of age 40+ years, the study included 5899 (80.5%) out of 7328 eligible individuals (mean age: 59.0±10.7 years; range: 40-94 years). - Primary and secondary outcome measures Hearing loss was examined in 5397 (91.5%) study participants, assessed using a standardised interview with questions from the ‘Hearing Handicap Inventory for the Elderly Screening Version (HHIE-S)’. - Results The prevalence of self-reported hearing loss (26.1%, 95% CI 24.2 to 27.2) increased from 10.9% (95% CI 8.0 to 13.7) in participants aged 40-45 years old to 59.0% (95% CI 51.6 to 66.4) in those aged 80+ years old. It was higher for men than for women in the 60-80 years age group (38.93%, 95% CI 35.8 to 42.1, vs 32.8%, 95% CI 30.2 to 35.3; p=0.003). On multivariable analysis, higher prevalence of hearing loss was associated with older age (p<0.001; OR [per year of age]: 1.06 [1.06 to 1.07]), male gender (p<0.001; OR: 1.26 [1.09 to 1.47]), higher depression score (p<0.001; OR: 1.06 [1.04 to 1.08]), higher prevalence of headache (p=0.001; OR: 1.27 [1.10 to 1.47]), history of cardiovascular diseases including stroke (p=0.001; OR: 1.32 [1.13 to 1.55]), and osteoarthritis (p<0.001; OR: 1.40 [1.18 to 1.67]), physically vigorous activity during work (p<0.001; OR: 1.40 [1.21 to 1.62]), alcohol consumption (p<0.001; OR: 1.51 [1.28 to 1.78]), and dry eye feeling (p<0.001; OR: 1.67 [1.30 to 2.16]). It was marginally correlated with a higher anxiety score (p=0.07; OR: 1.03 [0.998 to 1.06]). It was independent of diabetes (p=0.52), arterial hypertension (p=0.20), level of education (p=0.11), region of habitation (p=0.70), blood concentration of high-density lipoproteins (p=0.17) and low-density lipoproteins (p=0.52), current smoking (p=0.95) and smoking pack-years (p=0.37), and best corrected visual acuity (p=0.93). - Conclusions As in other countries the prevalence of hearing loss is high in this elderly population in Russia. It is primarily or secondarily associated with older age, depression, male gender, cardiovascular disease and alcohol consumption.
Gesehen am 18.09.2019